RANCANG BANGUN APLIKASI LEARNING MANAGEMENT SYSTEM DENGAN FRAMEWORK CODEIGNITER UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PADA SMK DARUL ISHLAH - Widyawati Widyawati; Ahmad Surahmat; Edy Nasri; Syahrul Febriyanto (Program Studi Sistem Informasi, Universitas Banten Jaya, 2022)
The learning process in Darul Ishlah Vocational High School is not optimal, student learning outcomes have not reached optimal, monotonous learning media, limited learning time, and delays in the learning process if the teacher concerned is unable to attend are the main things behind the research. Darul Ishlah Vocational High School require an innovative learning media that can be used to implement learning both face-to-face and online. So that the learning that is carried out can run as it should and the rate of student learning can increase and be able to explore the material provided by teacher and be able to increase student interest and learning outcomes in accordance with the targets set by the school. Therefore, one of the efforts to increase the effectiveness of learning that can be done is to implement a Learning Management System by combining face-to-face and online learning which is an alternative to learning process at Darul Ishlah Vocational School both in pandemic conditions and face-to-face learning processes. The purpose of this study was to test the effectiveness of the LMS implementation on the student learning process. System development in making applications using the method Waterfall. The modeling system used is the Unified Modeling Language (UML). In making applocations using PHP with the Codeigniter Framework as language scripting and the framework used to create applications, MySQL as the database. With this LMS, it is hoped that it can help the learning process become more effective, make it easier for teacher to distribute materials, assignment, exam questions to student. This LMS application can be used as an additional discussion medium for teacher and student to discuss unfinished subject matter, and a student can work on multiple-choice exam questions and collect assignments given by the teacher.